A Person of Interest: Gordon Childe and MI5 - Lever, Michael David (Buried History: The Journal of the Australian Institute of Archaeology, 2016)
Vere Gordon Childe is widely regarded as the single most influential thinker in the history of archaeology. He is almost certainly the most prolific author and widely published scholar that the discipline has seen. Yet, his fiercely independent original thinking and character did not come without cost to him. This paper begins with a brief introduction to Childe the man and academic. It then utilises recently released MI5 files to sketch new insights into Childe’s life and the different manner in which he was regarded by British and Australian Intelligence; the level of MI5 monitoring of Childe was intense. This paper draws attention to the scope that these intelligence files provides for further and more detailed biographical studies of Childe than was possible in this preliminary outline.